Enclosures as a land management tool for food security in African drylands. Issue 1 (2nd January 2019) - Nyberg, Gert; Mureithi, Stephen M.; Muricho, Deborah N.; Ostwald, Madelene
ABSTRACT: Increasing sedentary agro-pastoralist livelihoods may be explained by land degradation, population pressure, agricultural commodification, and economic development. We reviewed scientific and 'grey' literature for the effects of enclosures on food security. Only 8% of the 114 reviewed scientific articles addressed food production, while 69% approached environmental parameters that indirectly affect food security, most of which had positive results. Thirty-one percent focused on social and economic impacts, land tenure conflicts and elite capture with negative connotations. The 'grey' literature showed an opposite balance between positive environmental views and negative socio-economic impacts. Enclosures are not a panacea for dryland development, but their use need to be recognized and understood. Multidisciplinary research and cooperation on the applied management of enclosures in the context of food security is highly needed. Furthermore, agro-pastoralist land-use practices need more policy space and practical management support, such as clear tenure legislation, agroforestry methodologies, and support in fodder production systems.